The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0103-97332004000400003
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor quantum dot nanostructures and their roles in the future of photonics

Abstract: This paper discusses the growth and the properties of semiconductor nanostructures based on self-assembled quantum dots (QDs). These QDs confine electrons or excitons in zero-dimension (0D), similar to an artificial atom or to an artificial molecule in the case of coupled QDs with vertical alignment. They are obtained in a simple step during the epitaxy of strained III-V semiconductors such as InAs on GaAs, or InAs on InP. We will elaborate on the unique optical properties and the physics of self-assembled QDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…At present, different SQDs have been manufactured using different growth techniques and where it has been demonstrated that the optical properties exhibited by this type of structures have a strong influence of their morphology and the materials used in their manufacturing process. [5]. On the other hand, the optical solitons were observed for the first time in media that had a high absorption at specific wavelengths known as resonant optical media, but that at a certain minimum power the medium presented a transparent behavior, for this purpose it is known as self-induced transparency SIT.…”
Section: Theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…At present, different SQDs have been manufactured using different growth techniques and where it has been demonstrated that the optical properties exhibited by this type of structures have a strong influence of their morphology and the materials used in their manufacturing process. [5]. On the other hand, the optical solitons were observed for the first time in media that had a high absorption at specific wavelengths known as resonant optical media, but that at a certain minimum power the medium presented a transparent behavior, for this purpose it is known as self-induced transparency SIT.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Some of the most recent investigations indicate that this type of heterostructures can undergo abrupt changes in the spectral response with minimal variations in their size and morphology, offering important applications to optics, among which are the lasers of new generations, diodes. light emitters, optical multiplexers, biosensors, spectral tuners, quantum computing, logic gates, among others [1][2][3][4][5][6]. Nowadays, it has been possible to combine nanostructures with other polymeric materials such as optical fibers, giving rise to nanocomposites, which are generally composed of several phases such as SiO2, where one or several of its dimensions are found at the nanoscale [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the same study by Bugajski and Lewandowski in ref. 29, the doping concentration of n in cm −3 , resulting in spectral broadening of ΔE(n) in eV, can be determined with 10% uncertainty as in eqn (2).…”
Section: Cathodoluminescence Studiesmentioning
confidence: 99%
“…The use of semiconductor quantum dot (QD) structures for optoelectronics 1,2 and photovoltaics 3 is becoming more and more attractive. Due to a delta function like density of states and strong electron and hole confinement, QDs offer a low and temperature-insensitive threshold current density and a large band width for lasing.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum dots have discrete energy levels like those of a single atom. Therefore, novel optoelectronic devices such as the quantum dot laser [1] and the quantum dot infrared photodetector (QDIP) [2] have become feasible.…”
Section: Introductionmentioning
confidence: 99%